Pengaruh Subtitusi Lumpur Sidoarjo (LUSI) Terhadap Kuat Tekan Bata Beton (Paving Block) - Masbuhin Masbuhin (Universitas Islam Lamongan, 2020)
This study aims to determine the process of utilizing Sidoarjo Mud (LUSI) as a substitute for paving blocks and to determine the results of the compressive strength test of using LUSI as a substitute for paving blocks. The LUSI substitution is expected to be able to provide innovations in the construction of a paving block mixture. The research method used is the experimental method. The manufacture of test objects starts from the preparation stage, mix design, manufacture of test objects, testing and classifying paving blocks according to SNI 03-0691-1996. The sample of specimens used normal mix design and mix design substitute LUSI 40% of the fine aggregate value. Based on the results of research, paving blocks with a normal mix design of 1Pc: 2Ps are classified as quality A, 1Pc: 3Ps and 1Pc: 4Ps are classified as B quality, while for paving blocks substituting LUSI in a mixture of 1Pc: 2Ps is classified as quality B, for a mixture of 1Pc: 3Ps and 1Pc : 4Ps is classified as C quality. It can be concluded that the compressive strength of paving blocks has decreased in compressive strength after being substituted by LUSI, with a successive percentage value of 32%, 59% and 58%.